Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Bank Syariah - septia, elia; Fasa, Muhammad Iqbal; Suharto, Suharto (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
Service quality is the main basis for determining the level of customer satisfaction. In this case the company can be said to be good if it can provide goods or services in accordance with the wishes of customers. Product quality and good service efficiency will greatly affect customer satisfaction. Service quality is considered good if the service provided is in accordance with what consumers expect, and if it exceeds what consumers expect, then the service can be said to be very satisfied. However, sometimes the service does not meet consumer expectations. In a service must have an honest nature to the customer. In addition, creativity, courage, and self-confidence also reflect the willingness to try and seek new business opportunities, broad-minded and also updated with current news and information developments. The purpose of this study is to analyze the effect of service quality on customer satisfaction at Islamic banks.